2009
DOI: 10.1016/s0973-0508(09)80024-5
|View full text |Cite
|
Sign up to set email alerts
|

Disaster management of civilian gunshot head wounds in north Indian state

Abstract: Management of 3794 gunshot wounds of head at disaster scale, who presented to our emergency room in groups continuously over a period of 20 years, by the Department of Neurosurgery at Sher-I-Kashmir Institute of Medical Sciences (SKIMS) Kashmir, India, from September 1988 to November 2008, revealed an overall mortality of 87.69% (3327 out of 3794). Patients were triaged in emergency CT-room. Most of the victims were males. Most of the deaths 79.14% (2633 out of 3327) occurred within 30 minutes of the patient's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
(103 reference statements)
2
7
0
Order By: Relevance
“…In a study by Mansuco et al [11] in 40 subjects with CGW, 16 died and 3 survived among subjects with a GCS ≤8, whereas all subjects with a GCS score greater than 8 survived. Studies in CGW have shown that admission GCS is the cornerstone for the determination of prognosis and mortality in CGWs, and mortality increases as GCS decreases [10,14,17,20,26]. Our results were in accordance with the literature data.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In a study by Mansuco et al [11] in 40 subjects with CGW, 16 died and 3 survived among subjects with a GCS ≤8, whereas all subjects with a GCS score greater than 8 survived. Studies in CGW have shown that admission GCS is the cornerstone for the determination of prognosis and mortality in CGWs, and mortality increases as GCS decreases [10,14,17,20,26]. Our results were in accordance with the literature data.…”
Section: Discussionsupporting
confidence: 92%
“…İntraventricular hemorrhage, SAH, shift, and edema on CT are predictive of poor prognosis and increased mortality in penetrating CGWs [17,18,20,26]. The same CT findings were also correlated to poor prognosis and high mortality in our study.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In fact the non-metallic plastic, rubber, wax, stones and wooden missiles have proved more dangerous and fatal to control mobs and protesters 3,4,5,6,7 . Gunshot wounds of head are common in military personnel in war zones but for the past few decades civilian population around the world has become vulnerable to such injuries due to civil wars, regional conflicts, militancy, terrorism and military-related operations 8 . The rubber bullets were first used in 1970 by British Forces in Northern Ireland and were replaced by plastic bullets in 1972 by the British authorities.…”
Section: Introductionmentioning
confidence: 99%